Power in AI and public policy - Lena Ulbricht (Handbook on Public Policy and Artificial Intelligence, 2024)
This chapter asks: What is AI and how is it related to power relations? And what can those of us who study power contribute to the debate about public sector AI? The chapter starts by developing a systematization of different conceptions of power that encompasses various ontological and dimensional distinctions of power. The next section scrutinizes how these conceptions of power relate to dominant discourses about the power of AI in public policy: the use of AI in public policy, recent initiatives to regulate AI, and AI-riggered systemic criticism and propositions for new social orders and utopias. The final section discusses the implications of the insights for our understanding of power and public sector AI.
Keywords: 320; künstliche Intelligenz; Macht; öffentlicher Sektor; öffentliche Hand; politische Macht; Technokratie; Regulierung